Impact of Organizational Culture on Innovation: A Study of Demographic of Software Professionals - Vandana Bharti, Ruchi Khanna (International Journal of Scientific Research and Management (IJSRM), 2015)
The purpose of this study was to find out the significant difference of Organizational Culture and Innovation amongst different position and level of working experience in software industries. The survey method through the technique of questionnaire had been adopted to collect the relevant data for this study. The organizational culture questionnaire, which is adopted from Martins (1989, 1997). The original questionnaire consists of 89 items, but 40 items that were common to all the companies were included in the study. These 40 items are representative of the five determinants of the Organizational Culture. The innovation questionnaire is adopted from Abdul Razak Ibrahim, Ali Hussein Saleh Zolait, Sivadasan Subramanian and Ahmad Vazehi Ashtiani (2009). The original questionnaire consists of 48 items, but 20 items that were common to all the companies were included in the study. A Likert-type scale is used both the organizational culture and innovation. It is evident that the result of ANOVA shows that Organizational Culture and Innovation are significantly different amongst different positions in software industries. Similarly Organizational Culture and Innovation are significantly different amongst different level of working experience in software industries.